Vibrational spectra and structure of the cis and trans conformers of methyl nitrite: an ab initio MO study - Silva, João Bosco P. da (1996)
The vibrational and conformational properties exhibited by nethyl nitrite (CH3ONO) were studied by ab initio MO methods (HF-SCF and MP2) using both the 6-31G and 6-311G basis sets without or with the inclusion of diffuse and/or polarization functions. Fully optimized geometries, relative stabilities, dipole moments and harmonic force fields for both the cis and trans conformers of this molecule were determined and the results compared with available experimental data. In agreement with the experimental results, the calculations involving polarization functions at the MP2 level of theory indicate that the most stable conformer of methyl nitrite is the planar cis conformer, where the methyl group is eclipsing the NO bond, while the trans form was predicted to have a higher energy than this form by about 4 kJ mol−1. The conformational dependence of some relevant structural parameters was used to characterize the most important intramolecular interactions present in the studied conformers, and their calculated infrared spectra were used to review previous assignments of the experimentally observed bands for both the normal and deuterated (CD3ONO) species. Chemometrics methods (principal components and two-level factorial designing) were used both to analyze the effect of changing the basis set and level of theory used to perform the calculations, and to aid comparison between the experimental and calculated vibrational spectra